EFEKTIVITAS KEBIJAKAN BEBAS VISA KUNJUNGAN BAGI WARGA NEGARA REPUBLIK RAKYAT TIONGKOK TERHADAP KEAMANAN DAN KETERTIBAN DI INDONESIA - Muhammad Satrio; Muhammad Iqbal Zulfikar; Victorius Tarigan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The visa exemption policy in Indonesia has been implemented to promote tourism and economic growth by facilitating the entry of foreign nationals, including Chinese citizens. However, this policy has also raised concerns regarding its impact on security and public order. This study aims to analyze the effectiveness of the visa exemption policy for Chinese nationals in relation to security and public order in Indonesia. The research employs a normative-empirical legal method, combining a statutory and conceptual approach with the analysis of empirical data derived from official reports and news sources on immigration violations. The findings indicate that, although a clear legal framework supports the policy, its implementation shows a gap between normative provisions and practical enforcement. Empirical data reveal a significant number of immigration violations, including misuse of residence permits and overstays, with Chinese nationals among the most frequently involved groups. These results suggest that the effectiveness of the visa exemption policy remains limited, particularly in maintaining security and public order. In conclusion, while the policy contributes to economic objectives, it requires stronger immigration control mechanisms and more effective supervision to ensure a balance between economic benefits and national security.